2020
DOI: 10.2139/ssrn.3764500
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Personality Traits on University Performance: Evidence from Italian Freshmen Students

Abstract: D e s pit e s ev e ral at t e m pt s t o prov ide a de f ini t e pat t e rn re g arding t he e f f e ct s of pe rs onalit y t rait s o n pe rf orm a nc e in hig h e r e du c at ion, t he de bat e ov e r t he nat u re of t he re lat io ns hip is f ar f rom be i ng c onc lu s iv e . T he us e of dif f e re nt s u bje ct pools and s am pl e s ize s , as we ll as the u s e of ide nt if ic at ion s t rat e g ies t hat e it he r do not ade q u at e ly ac c ou nt for s e le c t ion bias o r are u nable t o e s t abli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 69 publications
1
2
0
Order By: Relevance
“…This was a somewhat expected result, as conscientiousness is one of the most important influencing factors on learning and academic achievement (O'Connor and Paunonen, 2007;Poropat, 2009). Also, conscientiousness was found to be highly correlated to student scores during the COVID-19 pandemic (Corazzini et al, 2020). Our results are in line with Komarraju et al (2009), and Müller et al (2006, who found that conscientiousness is a positive predictor of intrinsic motivation.…”
Section: Effects Of Conscientiousnesssupporting
confidence: 88%
See 2 more Smart Citations
“…This was a somewhat expected result, as conscientiousness is one of the most important influencing factors on learning and academic achievement (O'Connor and Paunonen, 2007;Poropat, 2009). Also, conscientiousness was found to be highly correlated to student scores during the COVID-19 pandemic (Corazzini et al, 2020). Our results are in line with Komarraju et al (2009), and Müller et al (2006, who found that conscientiousness is a positive predictor of intrinsic motivation.…”
Section: Effects Of Conscientiousnesssupporting
confidence: 88%
“…More "open" students may face more challenging and difficult situations that allow them to perceive more self-efficacy than students with a more "reserved" character. This conjecture is backed up by the result of Corazzini et al (2020) who found high levels of openness to new experiences correlating with better student scores during the COVID-19 pandemic. Moreover, openness correlated positively to intrinsic motivation, replicating the work of Komarraju et al (2009) and Önder et al (2014).…”
Section: Effects Of Opennessmentioning
confidence: 97%
See 1 more Smart Citation